Cross-Border WebGIS Database CURe MODERN. - Exner, Jan-Philipp; Wundsam, Timo; Noll, Rüdiger; Kebbedies, Guido (My University, 2015)
As part of the INTERREG IVa-research project CURe MODERN, a WebGIS-platform was developed, which enables a visual comprehension of studies done within the project. This project was realized in cooperation with the university of Kaiserslautern (TU Kaiserslautern), the Department of Computer Aided Design (CAD) & planning methods in urban planning and architecture, the Fraunhofer Institute for Nondestructive Testing (IZFP), the State Office for road construction in Saarland (LFS), the french associate CEREMA (Centre d études et d expertise sur les risques, l environnement, la mobilité et l aménagement) as well as the Eurodistrict SaarMoselle and the company of Rogmann engineers from 2012 - 2014. Aim of the project was to use non-destructive testing methods for infrastructural and cultural buildings and to make these results available for stakeholders of the german and french side. As a kind of an infrastructural and cultural database, this platform aims to communicate results and experiences within the project as well as between the members of the project and also to politicians and citizens. It can offer policymakers a tool to quantify problems and to clarify where possible weak spots could be present for various buildings. With the integration of three dimensional models inside the platform, details such as the need to repair certain parts of the buildings can easily be shown to any interested citizen. This easy understandable platform was developed without the use of special expensive GIS-software. It was created as a browser based system and so it works with any common computer and helps with the communication between different disciplines.
Keywords: Methode; Städtebau; Datenbank; Infrastrukturplanung; Kommunikation; Testmethode; 3D-Modell; Schadensdiagnose; Informationsaustausch